A Leakage-Based Beamforming Algorithm for Cognitive MIMO Systems via Game Theory - Zhao, Feng; Lv, Xuezhi; Chen, Hongbin (Journal of networks, 2013)
Cognitive radio has been recently proposed as a promising technology to achieve efficient use of spectrum resources. In this paper, we consider spectrum sharing in a MIMO system where several secondary users (SUs) share spectrum with a primary user (PU). A leakage-based beamforming algorithm is proposed via game theory. The objective is to maximize the sum throughput of SUs subject to the signal-to-leakage-and-noise ratio (SLNR) constraint of SUs and PU interference constraint. The sum-throughput maximization problem is formulated as a non-cooperative game, where the SUs compete with each other over the resources offered by the PU. Nash equilibrium is considered as the solution of this game. Simulation results show that the proposed algorithm can achieve a high sum throughput and converge to a locally optimal beamforming vector. Index Terms-beamforming, cognitive radio, MIMO, game theory, Nash equilibrium 1